Institutional Challenges to Community Development: The Case of Kobodi Administrative Area in the Mnquma Local Municipality, Eastern Cape, South Africa - Luleka Mkosi (E-Journal of Humanities, Arts and Social Sciences, 2025)
South Africa’s key community development challenge is to overcome the legacy of colonialism and apartheid, characterised by racially segregated settlement patterns and unequal distribution of resources. The black rural communities are impoverished because they were discriminated against in terms of the distribution and access to resources and infrastructure under the apartheid system. Regrettably, due to institutional challenges, community development efforts have not been able to significantly impact the rural social economies of disadvantaged communities. Therefore, the study investigated the institutional challenges that hamper community development in impoverished rural communities, using the Kobodi Administrative Area as the case under investigation. The study used a qualitative descriptive research method to generate and analyse the data. Therefore, probability and non-probability sampling techniques were used to select the 27 informants. The area has unequivocally identified the lack of agricultural services, poor infrastructure, unequal distribution of resources, and inadequate education as the primary barriers to community development. The study confidently recommends prioritising skills and knowledge development for community members and development practitioners as a necessary step toward overcoming these challenges. This study contributes to the scholarship on rural development and institutional challenges in post-apartheid South Africa by providing empirical insights from the Kobodi Administrative Area. It extends existing literature by critically illustrating how historical legacies of inequality, combined with present-day institutional inefficiencies, continue to undermine community development efforts in rural contexts. By identifying specific, the study offers a solid understanding of the structural and operational impediments to rural advancement.